The Impact of Work Connectivity Behavior on Employee Time Theft: The Role of Revenge Motive and Leader–Member Exchange - Cuiying Wang; Jianfeng Huang; Jianping Zhu (Behavioral Sciences, 2025)
Organizations have long been actively seeking ways to reduce unethical behavior among employees. However, employee time theft is widespread and costly across various industries, and related research remains relatively limited. Therefore, this study employed social exchange theory to empirically investigate how and when work connectivity behavior promotes employee time theft. Drawing on a sample of 330 employees, our findings indicate that work connectivity behavior positively impacts employee time theft by triggering revenge motives among employees. Furthermore, it was discovered that leader–member exchange weakens both the direct effect of work connectivity behavior on revenge motive and the indirect effect of work connectivity behavior on employee time theft via revenge motive. This research developed and elucidated a moderated mediation model, providing valuable insights for both theory and practice.